PRESERVATION STRATEGIES OF PAVEMENT BASED ON ROUGHNESS INDEX AND LIFE CYCLE COST - Karimi, Muh Bahrul Ulum Al; Mahfuda, Anno; Muthaher, Andi Muflih Marsuq (GEOMATE Journal, 2025)
The design life, traffic volume, regional conditions, quality specifications, and other factors are all taken into consideration by the pavement design standards implemented in several nations. The design eventually leads to the pavement's ability to serve as access to designated locations. For various reasons, the relationship between planning and operation often falls apart. However, the lack of comprehensive preparation for preservation and rehabilitation throughout road service life is one notable cause. After designating and forecasting the periods and expenses required during the pavement's service life, this study aims to offer an alternative perspective on planning. Both rigid and flexible pavements in new condition with a 40-year design life are the pavements that will be observed. In this instance, the International Roughness Index (IRI) will be used to estimate the pavement's functional bearing capacity. Preservation strategy is chosen to extend the service life of pavement to be 50th years. The Life Cycle Cost Analysis (LCCA) approach and the IRI value will be combined to create forecasts of the costs and schedule that will be incurred throughout the road's service life. The LCCA will utilize agency cost and user cost values. Compared to rigid pavements, agency costs are higher when flexible pavements are reconstructed. Rigid pavements are typically more costly than flexible pavements when considering other factors, including user cost. According to the research, rigid pavements are more effective for long-term pavement construction. Furthermore, this study would help stakeholders make decisions on road pavements.